Sex-Specific Linear Polyubiquitination Is a Critical Regulator of Contextual Fear Memory Formation - Musaus, Madeline; Farrell, Kayla; Navabpour, Shaghayegh; Ray, W. Keith; Helm, Richard F.; Jarome, Timothy J. (Frontiers in Behavioral Neuroscience, 2021)
Strong evidence supports that protein ubiquitination is a critical regulator of fear memory formation. However, as this work has focused on protein degradation, it is currently unknown whether polyubiquitin modifications that are independent of the proteasome are involved in learning-dependent synaptic plasticity. Here, we present the first evidence that atypical linear (M1) polyubiquitination, the only ubiquitin chain that does not occur at a lysine site and is largely independent of the proteasome, is critically involved in contextual fear memory formation in the amygdala in a sex-specific manner. Using immunoblot and unbiased proteomic analyses, we found that male (49) and female (14) rats both had increased levels of linear polyubiquitinated substrates following fear conditioning, though none of these protein targets overlapped between sexes. In males, target protein functions involved cell junction and axonal guidance signaling, while in females the primary target was Adiponectin A, a critical regulator of neuroinflammation, synaptic plasticity and memory, suggesting sex-dependent functional roles for linear polyubiquitination during fear memory formation. Consistent with these increases, in vivo siRNA-mediated knockdown of Rnf31, an essential component of the linear polyubiquitin E3 complex LUBAC, in the amygdala impaired contextual fear memory in both sexes without affecting memory retrieval. Collectively, these results provide the first evidence that proteasome-independent linear polyubiquitination is a critical regulator of fear memory formation, expanding the potential roles of ubiquitin-signaling in learning-dependent synaptic plasticity. Importantly, our data identify a novel sex difference in the functional role of, but not a requirement for, linear polyubiquitination in fear memory formation.